Nilai-nilai Sosial Masyarakat Pendatang Tapanuli Selatan dalam Pelaksanaan Pernikahan Menggunakan Tradisi Adat Tari Tor Tor Naposo Nauli Bulung di Wilayah Kota Bengkulu - Muhammad Safii Siregar; Ahmad Suradi; Moch. Iqbal (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2026)
Abstract : This study aims to: (1) describe the tradition of the Tor-Tor Naposo Nauli Bulung dance in the context of migrant community life in Bengkulu City; and (2) analyze the meaning and interpretation of the social values contained in the implementation of the Tor-Tor Naposo Nauli Bulung dance according to the perspectives of traditional leaders, dance performers, and the Tapanuli Selatan migrant community. This research uses a qualitative approach with a descriptive research type. Data collection techniques were carried out through observation, interviews, and documentation involving informants consisting of traditional leaders, dance performers, and members of the Batak Tapanuli Selatan community in Bengkulu City. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results of this study indicate that the tradition of the Tor-Tor Naposo Nauli Bulung dance plays an important role in the life of migrant communities, namely as: (a) a means of cultural preservation that is maintained despite being far from the homeland; (b) a symbol of ethnic identity of the Batak Tapanuli Selatan community in a different social environment; (c) a medium to strengthen social relationships and solidarity among members of the migrant community; and (d) a means of cultural education for the younger generation in understanding traditional customs.Furthermore, the meaning and interpretation of the social values contained in the implementation of the Tor-Tor Naposo Nauli Bulung dance include: (a) the value of togetherness and mutual cooperation reflected in collaboration among community members in every stage of the tradition; (b) the value of cultural preservation and ethnic identity shown through efforts to maintain traditions amid modernization; and (c) the value of respect for parents and ancestors, which is manifested through traditional procedures, dance movements, and polite behavior in the implementation of the tradition.Keywords: Tradition, Tor-Tor Dance, Naposo Nauli Bulung, migrant community, social values. Abstrak : Penelitian ini bertujuan untuk: (1) mendeskripsikan Tradisi Tari Tor-Tor Naposo Nauli Bulung dalam konteks kehidupan masyarakat perantauan di Kota Bengkulu; dan (2) menganalisis makna serta pemaknaan nilai-nilai sosial yang terkandung dalam pelaksanaan Tari Tor-Tor Naposo Nauli Bulung menurut pandangan tokoh adat, pelaku tari, dan masyarakat pendatang Tapanuli Selatan. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi dengan informan yang terdiri dari tokoh adat, pelaku tari, serta masyarakat Batak Tapanuli Selatan di Kota Bengkulu. Analisis data dilakukan melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa Tradisi Tari Tor-Tor Naposo Nauli Bulung memiliki peran penting dalam kehidupan masyarakat perantauan, yaitu sebagai: (a) sarana pelestarian budaya yang tetap dijaga meskipun berada jauh dari kampung halaman; (b) simbol identitas etnik masyarakat Batak Tapanuli Selatan di lingkungan sosial yang berbeda; (c) media untuk mempererat hubungan sosial dan solidaritas antaranggota masyarakat perantauan; serta (d) sarana pendidikan budaya bagi generasi muda dalam memahami adat istiadat. Selain itu, makna dan pemaknaan nilai-nilai sosial dalam pelaksanaan Tari Tor-Tor Naposo Nauli Bulung meliputi: (a) nilai kebersamaan dan gotong royong yang tercermin dalam kerja sama antaranggota dalam setiap pelaksanaan tradisi; (b) nilai pelestarian budaya dan identitas etnik yang terlihat dari upaya mempertahankan tradisi di tengah arus modernisasi; serta (c) nilai penghormatan terhadap orang tua dan leluhur yang diwujudkan melalui tata cara adat, gerakan tari, serta sikap sopan santun dalam pelaksanaan tradisi.Kata Kunci: Tradisi, Tari Tor-Tor, Naposo Nauli Bulung, masyarakat perantauan, nilai sosial.